Spectroscopic characterization of the oxyferrous complex of prostacyclin synthase in solution and in trapped sol–gel matrix - Yeh, Hui-Chun (2008)
Prostacyclin synthase (PGIS) is a member of the cytochrome P450 family in which the oxyferrous complexes are generally labile in the absence of substrate. At 4 °C, the on-rate constants and off-rate constants of oxygen binding to PGIS in solution are 5.9 × 10(5) m(−1) ·s(−1) and 29 s(−1), respectively. The oxyferrous complex decays to a ferric form at a rate of 12 s(−1). We report, for the first time, a stable oxyferrous complex of PGIS in a transparent sol–gel monolith. The encapsulated ferric PGIS retained the same spectroscopic features as in solution. The binding capabilities of the encapsulated PGIS were demonstrated by spectral changes upon the addition of O-based, N-based and C-based ligands. The peroxidase activity of PGIS in sol–gel was three orders of magnitude slower than that in solution owing to the restricted diffusion of the substrate in sol–gel. The oxyferrous complex in sol–gel was observable for 24 h at room temperature and displayed a much red-shifted Soret peak. Stabilization of the ferrous–carbon monoxide complex in sol–gel was observed as an enrichment of the 450-nm species over the 420-nm species. This result suggests that the sol–gel method may be applied to other P450s to generate a stable intermediate in the di-oxygen activation.